Sistem Informasi Pola Pembagian Jasa Pelayanan BPJS (Studi Kasus RSU Mayjen H.A. Thalib Kerinci) - FERDINAL R (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT The distribution system of BPJS service in hospitals or commonly called incentives is based on hospital leaders policy in terms of giving incentives to all hospital employees. Actually the distribution system used is not easy but it is also a very difficult distribution pattern. This division of services refers to the assessment of the index points of each employee. At Mayjen H.A. Thalib Kerinci Hospital data processing incentive division is still using the manual system so often cause constraints in the process of calculating the amount of incentives received by each Hospital employee. In this study to collect the required data using observation methods, interviews and literature study while the system development stage using a structured model in describing the functional model and in describing the data model. The system built later can accelerate the process of calculating the division of BPJS services at Mayjen H.A. Thalib Kerinci Hospital.